DIGITALIZING ISLAMIC BANKS: LEARNING FROM BANK SYARIAH MANDIRI - Hendri, Loni; Utami Fattah, sari (Faculty of Islamic Economics and Business, 2022)
This research aims to understand how BSM uses digital in its business development and what action other Islamic Bank could take from it to develop their digital utilization.Descriptivecritical analysis is used in this paper. The analysis began by presenting the understanding about digital role on Islamic Bank development and digitalization done by BSM. Analysis continued to digitalization done by BSM and its impact on Islamic Bank development so what action other Islamic Bank should do,what idea could be taken from it. Based on analysis, four things could be taken from BSM success using digital in its services: first, focus on young generation which can easily adapt with technology. Second, digital services improvement. Third, massive socialization. Forth, strong image of Islamic Bank built. Policy recommendation: first, strengthening regulation on safety and pleasure in digital-based transaction. Second, monitoring on shariah aspects in digital-based transaction offered by Islamic Bank.